Sustainable Aviation Energy and Environmental Issues - Karakoc, T. Hikmet; Ozerdem, M. Baris; Sogut, M. Ziya; Colpan, Can Ozgur; Altuntas, Onder; Açıkkalp, Emin (Springer International Publishing : Imprint: Springer, 2016)
This expansive reference on the use of clean energy technologies in the aviation industry focuses on tools and solutions for maximizing the energy efficiency of aircrafts, airports, and other auxiliary components of air transit. Key topics range from predicting impacts of avionics and control systems to energy/exergy performance analyses of flight mechanics and computational fluid dynamics. The book includes findings both from experimental investigations and functional extant systems, ranging from propulsion technologies for aerospace vehicles to airport design to energy recovery systems. Engineers, researchers and students will benefit from the broad reach and numerous engineering examples provided.